STUDENTS' CONCEPTUAL CHANGE AND SCIENCE PROCESS SKILLS ACQUISITION ON SEPARATION OF MIXTURE CONCEPT THROUGH PREDICT-DISCUSS-EXPLAIN-OBSERVE-DISCUSS-EXPLAIN (PDEODE) METHOD - Guatiani, Ineu (2013)
This study intended to examine the effectiveness of PDEODE (Predict-Discuss-Explain-Observe-Discuss-Explain) method benefits students learning on the degree to which students accept scientific concepts and use them to generate conceptual change and improve their science process skills. This study used a descriptive design and quantitative data collection method to investigate students' conceptual change and acquisition of science process skills on separation of mixture concept. The sample consists of 23 eight grade students in a bilingual secondary school. Students' conceptual change was evaluated by administering conception sheet contains open-ended question related to the separation of mixture concept, meanwhile students' acquisition of science process skills was evaluated through observation. After classroom intervention using PDEODE method was conducted, it revealed that the implementations of PDEODE method help students change their negative conception into positive conception about separation of mixture concept and there are two kinds of conceptual change patterns found on magnetic attraction concept, three kinds of conceptual change patterns found on decantation concept and two kinds of conceptual change patterns found on filtration and evaporation concept. PDEODE method influences the acquisition of science process skills on separation of mixture concept through hands on experiment. The highest acquisition is in conducting investigation skill, followed by followed by communicating skill, observing skill, predicting skill, inferring skill, applying concept skill, classifying skill, formulating hypotheses skill and the lowest percentage is questioning skill. Analysis of results indicates that PDEODE method can be effectively implemented to help students generate conceptual change and give information about students' acquisition of science process skills. Keyword: Conceptual Change, Science Process Skills. Penelitian ini bertujuan untuk menguji keefektifan metode PDEODE (Predict-Discuss-Explain-Observe-Discuss-Explain) pada pembelajaran siswa dalam tingkat siswa menerima konsep ilmiah dan menggunakannya untuk menghasilkan perubahan konseptual meningkatkan keterampilan proses sains. Penelitian ini menggunakan metode pengumpulan data kuantitatif dengan desain deskriptif untuk meneliti perubahan konseptual dan akuisisi keterampilan proses sains siswa pada konsep pemisahan campuran. Sampel penelitian ini tediri dari 23 siswa kelas delapan di sebuah sekolah menengah bilingual. Perubahan konseptual siswa dievaluasi melalui lembar konsepsi siswa yang mengandung pertanyaan open-ended berkaitan dengan konsep pemisahan campuran, sementara akuisisi keterampilan proses sains siswa dievaluasi melalui observasi. Setelah pembelajaran di kelas dengan menggunakan metode PDEODE dilakukan, terungkap bahwa penerapan metode PDEODE membantu siswa merubah konsepsi negatif pada konsep pemisahan campuran menjadi konsepsi positif dan ada dua jenis perubahan konseptual yang ditemukan pada konsep pemisahan campuran melalui daya tarik magnet, tiga jenis perubahan konseptual yang ditemukan pada konsep pemisahan campuran melalui penuangan dan dua jenis perubahan konseptual yang ditemukan pada konsep pemisahan campuran melalui penyaringan dan penguapan. Metode PDEODE mempengaruhi akuisisi keterampillan proses sains siswa melalui kegiatan eksperimen. Akuisisi tertinggi ditemukan pada kemampuan melaksanakan penelitian, kemampuan mengkomunikasikan, kemampuan mengamati, kemampuan memprediksi, kemampuan menarik keimpulan, kemampuan mengaplikasikan konsep, kemampuan mengklasifikasi, dan kemampuan merumuskan hipotesis, sementara akuisisi terendah ditemukan pada kemmpuan mengajukan pertanyaan. Analisis hasil penelitian mengindikasikan bahwa metode PDEODE dapat diterapkan secara efektif untuk membantu siswa menghsilkan perubahan konseptual dan memberikan informasi mengenai akuisisi keterampilan proses sains siswa. Kata kunci: Perubahan Konseptual, Keterampilan Proses Sains.